Peningkatan Kemampuan Berbicara Bahasa Inggris Mahasiswa MICE melalui Pendekatan Project-Based Learning (PBL) di Politeknik Negeri Jakarta - Safitry, Tantri Sari; Akbar, Djuni; Syafganti, Imam (Bisnis Event, 2025)
This study aims to assess the impact of implementing project-based learning (PBL) in English for Specific Purposes (ESP) classes at a vocational university. The research was conducted within the Business English department, with a specific focus on students majoring in Event Management or MICE (Meeting, Incentive, Convention, Exhibition) programs. The primary skill under investigation in this study is students' speaking abilities, particularly in the context of drama performance. A qualitative research approach was employed to explore the students' learning processes. Data collection methods included conducting semi-structured interviews, classroom observations, logbook entries, and evaluations of student performances, involving a total of 90 student participants. Subsequently, data analysis entailed an interpretation process and coding. the findings of this study reveal that the use of PBL in ESP classes significantly improved students' English-speaking skills, benefitting approximately 80% of the participants. Furthermore, the PBL approach not only enhanced speaking proficiency but also contributed to the development of discipline among students, motivating them to actively address learning challenges.